Temporary epicardial pacing wires in isolated Coronary Artery Bypass Graft: Necessity or force of habit? - Mian Mustafa Kamal; Abdul Ahad Sohail; Majid Osman; Shiraz Hashmi; Asma Altaf Hussain Merchant; Muhammad Musaab Munir; Hasanat Sharif (Journal of the Pakistan Medical Association, 2022)
Objectives: To determine the frequency of Temporary epicardial pacing wires usage and its predictors in the immediate postoperative period in isolated coronary artery bypass graft surgery. Method: The longitudinal study was conducted at the Aga Khan University Hospital, Karachi, from September 2019 to August 2020, and comprised adult patients of either gender who underwent isolated coronary artery bypass graft in the Department of Cardiothoracic Surgery. Demographic, peri-operative and post-operative Temporary Epicardial Pacing Wires use data was extracted from patient's files and the institutional electronic database. Logistic regression models were built to explore predictors of Temporary epicardial pacing wires usage. Data was analysed using SPSS 22. Results: Of the 322 cases evaluated, 27(8.4%) required the use of Temporary Epicardial Pacing Wires. Mean age of the patients requiring temporary epicardial pacing wires was 66.3±8.9 years compared to 58.7±8.9 years in those who did not require it (p<0.001), while the left ventricular ejection fraction percentage was 44.1±12.8 and 48.9±12.8 respectively (p=0.032). After adjusting for clinically plausible demographics and peri-operative variables, increasing age and low left ventricular ejection fraction were significantly associated with the use of temporary epicardial pacing wires in post-operative period of isolated coronary artery bypass graft patients (p<0.05). Conclusions: The frequency of temporary epicardial pacing wires usage in the post-operative period of coronary artery bypass graft was found to be low. Keywords: Arrhythmias, Adult cardiac surgery, Electrodes, Post-operative, Temporary Epicardial pacing.